The Effect Of Traditional And Industrial Nusa Tenggara Timur Smoked Curing “Se’i” On Levels LDL (Low Density Lipoprotein) Cholesterol In Experimental Animals (Study On Male Wistar Rats Induced With Pork Fat) (Journal of Namibian Studies : History Politics Culture, 2023)
Background : The prevalence of central obesity in Kupang City is higher than the prevalence in the province, which is 10.29%.It gets along with the escalation of pork se’i consumption which is estimated by Association of Farmer and Pork Entrepreneur that pork se’i production in some outlets in Kupang can reach 2,5 ton per day or more than 500 porks per day. The differences in physicochemical characteristics of industrial pig se'i and domestic pig se'i along with the potential for an increase in LDL cholesterol in individuals caused by the saturated fat content in pork se'i need to be observed in vivo.Objective : This study was to determine differences in LDL cholesterol in experimental animals before and after administration of pork se'i.Methods: This research is a true experimental with a pre-test and post-test controlled design was conducted using male wistar mice with weight 150-160 gram and age 8-12 weeks. The pork se’i was mixed with water with 1:17 concentration and given to the mice through oral sonde. The intervention was last for 30 days with daily intervention to the mice. Research subjects were divided into five groups, namely the positive control group, negative control group, and treatment at a dose of 0.89 gram/day; 1.78 grams/day; and 3.56 grams/day. The negative control group was given standard feed and drink ad libitum while the positive control group was induced using HFD (High Fat Diet) consisting of corn oil (80%), lard (5%), and chicken egg yolk (15%).Results : The average difference in LDL cholesterol levels after and before the intervention in all treatment groups was -9.44 mg/dl with the difference in average LDL cholesterol levels after and before the intervention being the highest in the control group. Independent T-Test analysis found that there was a significant difference between the group given a high-fat diet and the group given 1.78 grams of industrial pork se'i in one day marked with a significance result of 0.047